Evaluation of the Effect of Diet Containing Cinnamon and Red Pepper on Serum Biochemistry and Hematological Indices of Broiler (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
pepper on serum biochemistry and hematological indices of broiler. One hundred and twenty (120) day old broiler chicks (Ross 308) were randomly divided into 4 treatment groups and 3 replicates of 10 birds per replicate in a completely randomized design. A mixture of cinnamon and red pepper at the ratio of 1:1was put in broiler diets at 0%, 0.5%, 1.0% and 1.5% at starter and finisher stages and were fed to broilers for 8 weeks. At the end of the experiment, 3 birds per replicate were selected and used for analyses of serum biochemistry and haematological indices. Results of serum biochemistry showed significant (P
Keywords: Broiler; Cinnamon; Hematology; Red paper; Serum biochemistry